Possibility of Metaverse in Education: Opportunity and Threat - Tira Nur Fitria S.Pd., M.Pd; Nurmala Elmin Simbolon; Afdaleni (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This research investigates the possibility of a Metaverse between an opportunity or a threat in education. This is library research by using data from the source material (literature written in article journals) on the topic and synthesizing it into a coherent interpretation that highlights key issues. The result analysis shows the opportunity of Metaverse includes 1) Metaverse will probably make all activities in education can later be carried out in a virtual world. 2) New experiences of learning become more real and meaningful, so the students’ readiness is needed in applying Metaverse technology in education. 3) The teaching and learning process is regardless of time and space, so the processes are carried out in a wider and more active. The development of the technology of the Metaverse is essentially just a way, it cannot be used as the essence of life. The physical school/institutions and all the activities within it will also not be replaced by the Metaverse. Metaverse will only be a tool for the world of education to make services even better without having to eliminate everything in the real world. After all, the world of education aims to humanize humans, not virtualize humans. Along with the development of the Metaverse, this will have an opportunity and threat for humans. Therefore, we must be aware of the negative influence of Metaverse technology in education. This is a task for educators to have solutions for students to feel real learning. No technology can replace the role of the teacher